Leadership Development in Generation Z within Student Organizations - Rahma, Syifa Aurellia; Ayassy, Bayu Maulana; Abdillah, Syahbaruddin (Review: Journal of Multidisciplinary in Social Sciences, 2024)
The emergence of Generation Z, known as digital natives with a high level of adaptability to technology, flexibility, and active participation, presents both challenges and opportunities in leadership development within student organizations. This study aims to explore leadership approaches that align with the characteristics of Generation Z through a literature review method based on relevant scholarly journals. A qualitative descriptive approach using secondary data was employed to identify trends, gaps, and insights into effective leadership models in the context of student organizations. The literature review findings reveal that transformational and situational leadership styles are the most effective for Generation Z, as they emphasize inspiration, collaboration, empathy, and shared decision-making. Student organizations serve as strategic platforms for leadership practice through direct training in communication, time management, teamwork, and problem-solving. However, most previous studies have focused on corporate settings and have not thoroughly examined the dynamics of student organizations. Therefore, this literature study addresses an important gap by highlighting the need for a participatory, adaptive, and technology-based leadership model that is relevant to Generation Z. The study concludes that higher education institutions and student organizations must formulate contextual leadership strategies that support interpersonal communication and foster a positive organizational culture to maximize the leadership potential of Generation Z in facing future challenges.